A wall of our own : an American history of the Berlin Wall - Farber, Paul M., 1982- (The University of North Carolina Press, 2020)
"The Berlin Wall is arguably the most prominent symbol of the Cold War era, demarcating real and figurative divisions between east and west, Communism and capitalism, oppression and freedom. Its fall in 1989 is broadly understood as a pivotal moment in the history of the last century. For years afterward, tourists, locals, and even private businesses shipped fragments from the concrete structure around the world, turning it into a collectible commodity and cultural signifier for the triumph of Western democracy. As Paul Farber argues in framing this book, as the Wall was broken apart, it also solidified itself in the American imagination. But what was the nature and significance of this imaginary? In A wall of our own, Farber addresses this question from the moment of the Wall's creation to the present. He reveals how it has been both a literal and metaphorical presence in American culture, particularly influencing our discourse and ideas about breaking down barriers of race, class, gender, and sexual orientation"-- Provided by publisher
Keywords: Berlin Wall, Berlin, Germany, 1961-1989, in popular culture.; Berlin Wall, Berlin, Germany, 1961-1989, in art.; Berlin Wall, Berlin, Germany, 1961-1989, in literature.; Politics and culture -- United States -- History -- 20th century.; American literature -- 20th century -- History and criticism.; Arts, American -- 20th century.; Cold War -- Social aspects.; Mur de Berlin dans l'art.; Mur de Berlin dans la littérature.; Politique et culture -- États-Unis -- Histoire -- 20e siècle.; Littérature américaine -- 20e siècle -- Histoire et critique.; Arts américains -- 20e siècle.; Guerre froide -- Aspect social.; HISTORY -- United States -- 20th Century.